The Feasibility of EBUS-Guided TBNA Through the Pulmonary Artery in Highly Selected Patients. Issue 1 (January 2016) - Folch, Erik; Santacruz, Jose F.; Fernandez-Bussy, Sebastian; Gangadharan, Sidhu; Kent, Michael S.; Jantz, Michael; Stather, David R.; Machuzak, Michael S.; Gildea, Thomas R.; Majid, Adnan
Abstract : Background: The use of endobronchial ultrasound–guided transbronchial needle aspiration (EBUS-TBNA) for diagnosis and staging of benign and malignant thoracic disease has rapidly evolved into the standard of care. The lymph node stations that can be reached by EBUS and EUS are substantially more than those that can be accessed by mediastinoscopy. In rare cases, the clinician is faced with extraordinary circumstances in which a minimally invasive approach to the lymph nodes in station 5 is required. We present our findings in 10 cases, at 7 different institutions, where EBUS was instrumental in reaching a diagnosis. Methods: We retrospectively collected 10 cases where EBUS-TBNA was performed through the pulmonary artery in an attempt to reach the territory of lymph node station 5. All cases were performed by experienced interventional pulmonologists at 7 tertiary care centers in the United States and Canada. We describe the patients' demographics, comorbidities, complications, and cytopathology. Results: A definitive diagnosis was reached in 9 of the 10 patients. One case showed atypical cells and required a confirmatory Chamberlain procedure. No complications occurred as a result of careful transpulmonary artery needle aspiration. Conclusions: This multicenter case series suggests that transpulmonary artery needle aspiration guided by EBUS is possible and safe in the hands of experienced interventional pulmonologists. It is important to recognize that this is not an alternative to left VATS or Chamberlain procedure, but a last resort procedure. Abstract : Supplemental Digital Content is available in the text.